Religiosidade, felicidade e satisfação com a vida de idosas institucionalizadas - Lucca, Nádia (2020)
The world population is growing substantially, which has had important implications for the whole of society. Responding to this demographic change will require adaptations in many aspects of society, and the necessary understanding of the nature and implications of this transformation, in order to promote successful aging. Aging is focusing attention on factors that appear to be modifiable and that can have a favorable influence on the conditions of future life. There is evidence that religiosity and spirituality have a significant influence on these factors. In view of this scenario, the objective of this research was to verify the association of religiosity with the self-perception of happiness and overall satisfaction with the lives of elderly people living in Long-Term Institution. Cross-sectional study, part of the research “Patterns of aging and longevity: biological, educational and psychosocial aspects”, developed by the Graduate Program in Human Aging at the University of Passo Fundo (UPF) and linked to the National Academic Cooperation Program (PROCAD / CAPES). The sample in this study was composed of women aged 60 years or older; ILPI residents in the municipalities of Passo Fundo, Carazinho and Bento Gonçalves Long-Term Institution, totaling 80 elderly participants, who scored in the minimum scores of the Mini Mental State Examination, considering schooling. The data, stored in a database, were obtained from a questionnaire consisting of 23 blocks, considering, in this study, the variables of the blocks: A (identification), B (sociodemographic), C (cognitive evaluation), N (global satisfaction with life and referenced to domains), Q (religiosity). The results were presented in the form of two scientific productions. Scientific Production I, aimed to identify the importance and the meaning attributed to religiosity / spirituality by the elderly residents in Long-Term Institution. Which allowed recognizing the prevalence of the Catholic religion (78%), followed by the evangelical religion (15%) and the importance of religion in life (92%). As for the sense of religiosity / spirituality for the elderly, it was possible to observe a higher frequency for the variable a lot (57%) in relation to the strengths to face the difficulties of life and (42%) for the meaning of life. Scientific Production II, which sought to verify the association of religiosity with the self-perception of global satisfaction with the life and happiness of elderly women residing in a Long-Term Institution for the Elderly, showed that the more religious and / or spiritualized elderly women (56.3 %) expressed having a better self-perception of happiness (75%), and elderly women who feel happier expressed greater satisfaction in relation to family, friends and the environment. These results can constitute subsidies for professionals who work at ILPI to plan care actions that focus on the expression of religiosity / spirituality as an important dimension in comprehensive health care for the elderly.